Pengaruh Faktor Ekonomi Makro Te Pengaruh Faktor Ekonomi Makro Terhadap Kinerja Saham Di Pasar Modal Global - ficeroy, recky (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
This research investigates the influence of macroeconomic factors, such as inflation, interest rates and the rupiah exchange rate on stock performance in the global capital market. By using careful statistical analysis, this research identifies the relationship and impact of these economic variables on stock price movements on various stock exchanges throughout the world. The findings of this research provide valuable insight for investors and capital market practitioners in anticipating and managing risks and making more appropriate investment decisions amidst the dynamics of the global economy.